(untitled) (Medical Forum Monthly, 2020)
Objective: To find frequency of congenital coronary artery anomalies in patients, undergoing coronary angiography. Study Design: Observational Cross Sectional study. Place and duration: This study was conducted at the Cardiac Catheterization Laboratory of Lady Reading Hospital Peshawar from March 2009 to March 2020. Materials and Methods: In this study, a total of 21,362 coronary Angiographies were performed for work up of Coronary artery disease. Results: Coronary Artery Anomalies were found in 1.9% (n=405) patients. Mean age was 48.5±12.5 years. Males were 69.2% (n=280) and female were 30.7 %( n=124). The most common anomaly was anomalous origin of Right Coronary Artery from posterior sinus of Valsalva. It was found in 38.5% (n=156) patients. The diagnostic catheter used was Judkin Right 4, while in 15 patients, it was engaged with Amplatz Right catheter, AR 1. Second most common anomaly was separate origin of Left Anterior Descending artery and Left Circumflex artery. It was found in 30.7%(n=124) patients. All were engaged with Judkin Left, JL 4 Catheters. The third most common anomaly was abnormal origin of Left Circumflex from right sinus of Valsalva in 15.3%(n=62). All were engaged with Judkin Right 4 catheters except in 15 cases, which required 3DRC. Anomalous origin of Right Coronary Artery from left sinus of Valsalva was found in 11.5%(n=46) patients. All were engaged with JL 4 catheters. Only 1% (n=4) patients had LAD-RV fistula. All were engaged with Judkin Left 3.5 catheter. Conclusion: Coronary artery anomalies were rare findings in adults. Most common anomaly was the anomalous origin of Right Coronary Artery from posterior sinus.